IS ARTIFICIAL INTELLIGENCE A LEGAL SUBJECT IN CIVIL LAW? - Petrova, Mila (E-Journal VFU, 2025)
The report aims to examine the legal personhood of artificial intelligence (AI) from the point of view of civil law. Artificial intelligence has become one of the fastest growing fields of science. This new technology will penetrate and transform all areas of human life at a speed for which the legal system of no country in the world is prepared. The challenge for humanity is not whether to accept or reject these innovative technologies, but to quickly adapt to the new reality they offer us. The artificial intelligence systems can be trained, can make independent decisions, which is why in the future they are expected to be entrusted with so many aspects of the daily lives of human beings. This will inevitably necessitate an answer to the question of whether artificial intelligence can be recognized as a civil legal status as an independent participant in civil turnover. An analysis is made of what the legal subject is and whether AI has the same individualizing features.